ASSESSMENT OF DOCUMENTATION, ORGANIZATION, AND OUTCOMES OF OCCUPATIONAL SAFETY AND HEALTH TRAINING FOR HEALTHCARE WORKERS AT A DISTRICT HEALTH CENTER IN PHU THO PROVINCE, 2024 (Vietnam Journal of Community Medicine, 2026)
Background: Healthcare workers are frequently exposed to occupational hazards, including infectious agents, chemicals, and sharps. Occupational safety and health training is an essential measure to reduce occupational accidents and diseases. However, its implementation in district-level healthcare facilities remains limited.Objectives: To assess the status of documentation, organization, and outcomes of occupational safety and health training for healthcare workers at a district health center in Phu Tho Province in 2024.Methods: A cross-sectional study was conducted by reviewing all occupational safety and health training records at the center in 2024, including training plans, trainee lists, training materials, trainer records, and training monitoring logs. Data were analyzed using descriptive statistics.Results: The center had 324 employees, including one staff member in charge of occupational safety and health. Training facilities were inadequate, with a lack of standard practice rooms, and trainers had not obtained professional training certificates. The training participation rate was 32.9%; heads of units and staff responsible for occupational safety and health did not participate. Among trained participants, only 73.8% passed the post-training assessment.Conclusion: OHS training at the primary healthcare level still faces substantial limitations in terms of human resources, facilities, and organization. A comprehensive strategy is needed to improve training effectiveness in the future.
Keywords: Occupational health and safety; Training; Healthcare workers; District level; Situation assessment.